Socialisation of Building Adolescent Ethics towards Peers in Junior High School Children of State 2 Sragen - Natasya Odelia, Natasya Odelia (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2024)
Interaction occurs when humans meet other humans who are nearby both in the living environment and in external environments such as schools. In the process of interaction, the ethics of the individual will be seen, because ethics as a means of controlling a person to perform an action or word when interacting with others. Someone who lacks ethics when interacting with others will be less accepted by the surrounding people. Ethics is an attitude of courtesy that regulates humans in an environment that is in accordance with existing values and norms. The method used in this socialisation is lecture. In this socialisation, the subjects are teenagers of class VII F SMPN 2 Sragen. This socialisation aims to teach teenagers how to be ethical with their peers.